Use of microsatellite markers to evaluate the genetic diversity of local cassava landraces - Pedri, Eliane Cristina Moreno de; Cuchi, Giovana; Tiago, Auana Vicente; Rossi, Ana Aparecida Bandini (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2024)
Cassava is cultivated by family farmers who preserve local landraces in their proprieties, acting as guardians of this genetic resource. The existing genetic diversity for the species can be estimated using microsatellite molecular markers. Thus, the objective was then to carry out the molecular characterization of four local varieties of cassava (Cacau Branca, Cacau Roxa, Cacau Amarela and Mandioca Pão) cultivated by family farmers in the municipality of Apiacás, Mato Grosso state, Brazil using microsatellite markers. Four local landraces of cassava were sampled, totaling 40 individuals. Leaf material was used for DNA extraction and PCR amplification. A total of 67 alleles were amplified, with SSRY126 and SSRY21 amplifying the highest and lowest number of alleles, respectively. Among the amplified alleles, 33 rare alleles (49%) were identified. The observed heterozygosity (0.840) was higher than the expected heterozygosity (0.643), reflecting negative fixation indices. Loci with PIC values above 0.5 were GA12, GA131, GA140, SSRY27, SSRY28, and SSRY126. The dendrogram formed by the UPGMA hierarchical clustering generated five genetic clusters, which were in agreement with the Bayesian analysis. Thus, genetic diversity was observed among the local landraces cultivated in the family farmers’ fields in the municipality of Apiacás. The AP5 and AP20 individuals are the most genetically divergent among the analyzed group, and the Mandioca pão landrace is the most genetically distant from the other three landraces.